The Effect of Word of Mouth and Brand Image through Brand Trust on Purchasing Decisions for MS Glow Skincare Products in Bangkinang Kota, Kampar Regency - Saniah, Badriati; Noviasari, Henni; Alvionita, Agnes; Siregar, Prima Andreas (West Science Business and Management, 2025)
This study was conducted with the aim of knowing the effect of Word of Mouth and Brand Image through Brand Trust on Purchasing Decisions for Ms Glow Skincare Products in Bangkinang Kota, Kampar Regency. The population in this study were consumers of MS Glow skincare products in Bangkinang Kota, Kampar Regency, with the sample criteria in this study being MS Glow Skincare Product User Consumers, Consumers who live in Bangkinang Kota, Aged over 17 years. This study will use non-probability sampling techniques, where each member of the population does not have the same opportunity to be selected as part of the sample so that the sample size of this study is 100 people from the total population. The data analysis method of this study uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis method with SmartPLS software version 4.0.  The results of this study indicate that Word of Mouth affects the brand trust of Ms Glow skincare products, Brand Image affects the brand trust of Ms Glow skincare products. Word Of Mouth affects the purchase decision of Ms Glow skincare products, Brand Image affects the purchase decision of Ms Glow skincare products, Brand trust affects the purchase decision of Ms Glow skincare products, Word of mouth affects purchasing decisions through brand trust of Ms Glow skincare products, Brand image affects purchasing decisions through Ms Glow skincare brand trust.